A maintenance strategy for two-dimensional extended warranty based on dynamic usage rate. Issue 19 (2nd October 2017) - Tong, Peng; Song, Xuefeng; Zixian, Liu
Abstract : Maintenance strategies are commonly used for repairable products or items to reduce the warranty cost in the warranty coverage. This study proposes a new warranty maintenance strategy for two-dimensional extended warranty (EW) based on dynamic usage rate. Unlike previous studies that assumed a constant usage rate, the present study regards the consumer usage rate as dynamic in the two-dimensional EW coverage. A maintenance model is constructed to determine the optimal maintenance degree of warranty claim points and help service providers accurately estimate and reduce warranty cost. A numerical example of an automobile made in China is discussed to demonstrate the effectiveness of the proposed model. The formulated model can effectively reflect the changes in the consumer usage rate and thus helps service providers develop an accurate maintenance strategy. Meanwhile, the developed model can better reduce warranty cost compared with maintenance strategies with minimal repair.